Fear of stagnation? A review on growth imperatives - Oliver Richters; Andreas Siemoneit (Vereinigung für Ökologische Ökonomie (VÖÖ), 2017)
Worldwide economic growth is fostered, despite its severe conflicts with sustainability and despite the tendency of secular stagnation. To study whether this fostering is 'only' a question of political and individual will or 'unavoidable' to maintain economic stability, we deliver a rather narrow micro level definition of a 'growth imperative'. We divide the many alleged growth imperatives into five categories and review them, thereby reducing several reasonings to few core arguments. We conclude that neither commercial competition, nor profit expectations, nor the monetary system are stand-alone growth imperatives. Instead, when technological innovations (based on resource consumption) are introduced, market forces lead to a systematic necessity to net invest due to the interplay of creative destruction, profit maximization, and the need to limit losses. Unemployment is substantially caused by productivity gains, and the societal and political necessity of high employment explains why states 'must' foster economic growth. This explanation is culturally and normatively parsimonious and empirically substantiated. – – Weltweit wird Wirtschaftswachstum gefördert, trotz ernsthafter Konflikte mit Nachhaltigkeit und trotz der Tendenz zur säkularen Stagnation. Um zu untersuchen, ob dies 'nur' eine Frage politischen oder persönlichen Willens ist oder 'unvermeidlich' zur Bewahrung ökonomischer Stabilität, liefern wir eine relativ enge Definition eines 'Wachstumszwangs' auf der Mikroebene. Wir teilen die zahlreichen angeblichen Wachstumszwänge in fünf Kategorien ein und untersuchen sie kritisch, wobei wir verschiedene Argumentationen auf wenige Kernaussagen zurückführen. Wir kommen zu dem Schluss, dass weder wirtschaftlicher Wettbewerb noch Gewinnerwartungen oder das Geldsystem eigenständige Wachstumszwänge hervorrufen. Wenn hingegen technische Innovationen (basierend auf Ressourcenverbrauch) eingeführt werden, führen Marktkräfte im Zusammenspiel von schöpferischer Zerstörung, Gewinnmaximierung und Verlustbegrenzung zur systematischen Notwendigkeit von Nettoinvestitionen. Arbeitslosigkeit wird im Wesentlichen durch Produktivitätsfortschritte ausgelöst, und die gesellschaftliche und politische Notwendigkeit von Vollbeschäftigung erklärt, warum Staaten Wachstum geradezu fördern 'müssen'. Diese Erklärung ist kulturell und normativ sparsam und empirisch untermauert.
Keywords: Q01; O40; O44; P10; P1; 330; Wachstumszwang; Nullwachstum; säkulare Stagnation; Geldsystem; Wettbewerb; Profit; technischer Fortschritt; growth imperative; zero growth; secular stagnation; monetary system; competition; profit; technological progress